Clinical guidelines for oral appliance therapy in the treatment of snoring and obstructive sleep apnoea. (December 2013) - Ngiam, J; Balasubramaniam, R; Darendeliler, MA; Cheng, AT; Waters, K; Sullivan, CE
Abstract The purpose of this review is to provide guidelines for the use of oral appliances (OAs) for the treatment of snoring and obstructive sleep apnoea (OSA) in Australia. A review of the scientific literature up to June 2012 regarding the clinical use of OAs in the treatment of snoring and OSA was undertaken by a dental and medical sleep specialists team consisting of respiratory sleep physicians, an otolaryngologist, orthodontist, oral and maxillofacial surgeon and an oral medicine specialist. The recommendations are based on the most recent evidence from studies obtained from peer reviewed literature. Oral appliances can be an effective therapeutic option for the treatment of snoring and OSA across a broad range of disease severity. However, the response to therapy is variable. While a significant proportion of subjects have a near complete control of the apnoea and snoring when using an OA, a significant proportion do not respond, and others show a partial response. Measurements of baseline and treatment success should ideally be undertaken. A coordinated team approach between medical practitioner and dentist should be fostered to enhance treatment outcomes. Ongoing patient follow‐up to monitor treatment efficacy, OA comfort and side effects are cardinal to long‐term treatment success and OA compliance.